Nurses On The Frontlines: Stories Of Courage And Dedication During Global Health Crises (Journal of Namibian Studies : History Politics Culture, 2022)
Nurses have consistently demonstrated remarkable courage and dedication while serving on the frontlines during global health crises. This abstract delves into the narratives of these unsung heroes, highlighting their extraordinary efforts and sacrifices amidst adversity. Through the lens of various crises, including the COVID-19 pandemic, Ebola outbreaks, natural disasters, and conflict zones, this abstract explores the profound impact of nurses' resilience and compassion in safeguarding public health.